MEMES AND MEMERS: A QUALITATIVE DESCRIPTIVE STUDY ON THEIR CULTURE IN TAMIL NADU - G., Kavitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The internet’s spread is now becoming more widespread and diverse. Information can be obtained quickly, and meme content, for example, is widely disseminated via social media accounts (Purwaningrum & Sudana, 2020). There are a plethora of memes floating around on social media networking sites. It is gaining more popularity not only in Tamil Nadu, India but all over the world, with the help of apps like WhatsApp. Because meme creation has become the most popular form of entertainment, there is a high demand for meme creators in Tamil Nadu. Memers (Meme Creators) have earned their place in the same way that Doctors, Engineers, and Teachers have. They are the Golden Key that binds the people together (Mruthula, 2017). This study describes the evolution and Pioneers of meme culture in Tamil Nadu, as well as the various types of meme creators in Tamil Nadu. This study is qualitative descriptive and exploratory in nature.